Introducing ragi in the PDS is fraught with challenges - Pradhan, Mamata; Roy, Devesh (2018)
After a gap of three years, the Karnataka government has reintroduced ragi/finger millet in its public distribution system (PDS). To feed the PDS system, the government has announced a procurement price much higher than the market price and introduced bonuses. With interventions on the sides of both production as well as consumption, the objectives are to improve nutrition and increase the climate-resilience of agriculture since ragi is a drought-resistant crop and to improve returns for the farmer.